Border Dispute between Nepal and India - Paudyal, Gyanendra (Researcher: A Research Journal of Culture and Society, 2014)
Boarder between countries is a sensitive issue, which may leads to dispute. Sometimes, debate on boarder creates the situation of war between two countries. Boarder dispute cannot only divide the people of two countries but also the national politics. In this article, boarder dispute of Nepal with its neighbors is analyzed through historical and cultural perspective. This study is based on documentary sources. DOI: http://dx.doi.org/10.3126/researcher.v1i2.9884 Researcher 1(2) 2013: 35-48